2001
DOI: 10.1097/00003727-200110000-00009
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition Communication for a Latino Community

Abstract: Formative research techniques were used to develop a tailored health communication nutrition intervention for Latinas and their families. Members of the target community were recruited to participate in focus groups, depth interviews, and participant observations. Women, in particular, were observed preparing meals in their homes and purchasing groceries. The objective was to identify variables that could be used for targeting, segmenting, and tailoring the intervention. Results from these efforts were used to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 12 publications
2
42
0
Order By: Relevance
“…28 In addition, the use of multiple data collection methods during formative research has been recommended in this type of study. [29][30] We carefully selected several methods appropriate to the information gaps and needs of the trial. The use of methodological instruments and stakeholders' triangulation was useful to a) understand the problem from different points of view, b) better understand the school environment, c) corroborate and explain information within methods, d) develop a comprehensive matrix of the situation, e) guide the intervention selection, and g) to assess the feasibility and acceptability of the intervention by different stakeholders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…28 In addition, the use of multiple data collection methods during formative research has been recommended in this type of study. [29][30] We carefully selected several methods appropriate to the information gaps and needs of the trial. The use of methodological instruments and stakeholders' triangulation was useful to a) understand the problem from different points of view, b) better understand the school environment, c) corroborate and explain information within methods, d) develop a comprehensive matrix of the situation, e) guide the intervention selection, and g) to assess the feasibility and acceptability of the intervention by different stakeholders.…”
Section: Discussionmentioning
confidence: 99%
“…These and other advantages of using multiple methods in formative research, including the understanding of the cultural and ethnic diversity of the targeted audience, have been published elsewhere. [30][31] Our formative research showed that the school environment restricts opportunities for healthy eating, and enhances opportunities to consume highly energy dense foods and sugary beverages, promoting a positive energy imbalance. The important role of the school environment in sustaining energy imbalance that leads to overweight and obesity in school children has been documented.…”
Section: Discussionmentioning
confidence: 99%
“…42 We used well-established qualitative intervention development methods to adapt the intervention materials to the target Baystate study population. 43,44 Specifically, modifications to the intervention materials were informed by the literature, the cultural expertise of the study team, and focus groups of participants recruited from the Baystate study population. The focus groups gathered data on contextual factors impinging on physical activity levels, facilitators of physical activity, and participant reactions to the intervention materials.…”
Section: Formative Development Of the Interventionmentioning
confidence: 99%
“…Sussner and colleagues 10 found that immigrant Latina mothers face several barriers in the United States in preventing childhood obesity: larger portion sizes; increased access to unhealthy foods; attitudes supporting child overweight; and more time spent in sedentary activities. Cultural beliefs and norms may also influence the foods that Latina parents make available, [11][12][13][14][15][16] modeling of dietary behaviors and food-related parenting styles, 4,[17][18][19] beliefs about child weight, 5,16,20 and the meaning imparted to foods. 21 However, these behaviors and beliefs are likely rooted in more deeply held, underlying cultural values and norms, which are shaped by parents' cultures of origin as well as their immigration experiences and personal identities.…”
Section: Introductionmentioning
confidence: 99%